Semiconductor materials for gas sensing applications - Tan, Ooi Kiang (2008)
In this thesis, solid solution of mixed zirconium oxide and iron oxide for the application of gas sensing are studied. In this study on semiconductor oxide based gas sensors, the high-energy ball milling technique was used to prepare the nano-sized powders.